STRATEGI PEMBELAJARAN KURIKULUM MERDEKA BELAJAR DI MADRASAH IBTIDAYAH NEGERI SE KUBU RAYA - Salito (STKIP Subang, 2024)
The independent curriculum is one of the most important parts of education to activate students again, supported by a good strategy, learning will be more effective, in this the method used is descriptive qualitative, the data collection technique uses observation and interviews, while the subjects in this study are teachers at the State Ibtidaiyah madrasah in Subu Raya, the results of the research on the independent learning curriculum use various learning strategies including the Expository Learning Strategy. Discovery Learning Strategy. Mastery Learning Strategy. Inquiry Learning Strategy. Problem-Based Learning Strategy. Contextual Learning Strategy (Contextual Teachig Learning). Affective Learning Strategies. Cooperative Learning Strategies. Thinking Ability Enhancement Learning Strategy. Keywords: Learning Strategy, Merdeka Belajar Curriculum